2014
DOI: 10.5009/gnl13406
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Aldo-Keto Reductase 1B10 Is an Independent Predictor of Favorable Prognosis in Patients with Hepatocellular Carcinoma

Abstract: Background/AimsUpregulation of aldo-keto reductase 1B10 (AKR1B10) through the mitogenic activator protein-1 signaling pathway might promote hepatocarcinogenesis and tumor progression. The goal of this study was to evaluate the prognostic significance of AKR1B10 protein expression in patients with hepatocellular carcinoma after surgery.MethodsA tissue microarray was used to detect the expression level of AKR1B10 protein in tumors from 255 patients with hepatocellular carcinoma who underwent curative hepatectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…Silencing of AKR1B10 with siRNA suppresses HCC tumor growth [ 30 ]. Although the expression of AKR1B10 is increased in primary HCC tumors, several studies indicate that AKR1B10 is paradoxically correlated with the less aggressive and well-differentiated HCC tumors [ 23 , 31 33 ]. These results suggest that decreased expression of AKR1B10 is associated with the more advanced and malignant HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of AKR1B10 with siRNA suppresses HCC tumor growth [ 30 ]. Although the expression of AKR1B10 is increased in primary HCC tumors, several studies indicate that AKR1B10 is paradoxically correlated with the less aggressive and well-differentiated HCC tumors [ 23 , 31 33 ]. These results suggest that decreased expression of AKR1B10 is associated with the more advanced and malignant HCC.…”
Section: Introductionmentioning
confidence: 99%
“…After full-text review, 12 articles were excluded. Eventually, we identi ed 11 articles published between 2014 and 2019, which were included in the nal analysis [5][6][7][8][9][10][11][12][13][14][15]. The ow diagram of the literature search is shown in Fig1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies have shown that AKR1B10 is characterized by obvious carcinogenicity and can be used as a tumor marker [4]. Recently, an increasing number of studies showed that abnormal expression of AKR1B10 is signi cantly correlated with the prognosis of certain solid tumors [5][6][7][8][9][10][11][12][13][14][15]. However, the currently available results are inconsistent, and the prognostic value of AKR1B10 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These reports collectively emphasize that AKR1 isozymes such as AKR1B10 and AKR1B8 may play a vital role in modulating the development of ulcerative colitis and colitis-associated colorectal cancer in mammals. However, the mechanisms underlying AKR1B10 overexpression in many non-digestive tract cancers [12,13,15,18] are still not well elucidated, therefore efforts are needed to discover the relationship between AKR1B10 overexpression and cancer formation.…”
Section: Akr1b10 In Cancer Formationmentioning
confidence: 99%
“…On the contrary, the expression of AKR1B10 is downregulated in gastrointestinal cancer [16,17]. AKR1B10 overexpression has been considered as a valuable biomarker and prognostic indicator for some cancers [15,17,18], and low expression of AKR1B10 has been used as a biomarker for the diagnosis of bowel diseases (US8551720) [19]. AKR1B10 is a protein secreted through a lysosome-mediated pathway and may serve as a potential serum marker for malignant diseases [20].…”
Section: Introductionmentioning
confidence: 99%